(1)4(m2+n)+2(n-2m2),
=4m2+4n+2n-4m2,
=6n;
(2)5ab2-[a2b+2(a2b-3ab2)],
=5ab2-(a2b+2a2b-6ab2),
=5ab2-a2b-2a2b+6ab2,
=-3a2b+11ab2;
(3)3A-2B=3(x2-3x-6)-2(2x2-4x+6),
=3x2-9x-18-4x2+8x-12,
=-x2-x-30,
当x=-1时,原式=-x2-x-30,
=-(-1)2-(-1)-30,
=-1+1-30,
=-30;
(4)根据题意得,x+1=0,y-
1
2]=0,
解得x=-1,y=[1/2],
根据数值转换器列式,(x2+2y+1)÷2,
=[(-1)2+2×[1/2]+1)÷2,
=[3/2];
(5)(2x2+ax-y+6)-(2bx2-3x+5y-1),
=2x2+ax-y+6-2bx2+3x-5y+1,
=(2-2b)x2+(a+3)x-6y+7,
∵代数式的值与字母x所取的值无关,
∴2-2b=0,a+3=0,
解得a=-3,b=-1,
[1/3]a3-2b2-([1/4]a3-3b2),
=[1/3]a3-2b2-[1/4]a3+3b2,
=[1/12]a3+b2,
=[1/12]×(-3)3+(-1)2,
=-[9/4]+1,
=-[5/4].